Editorial - Nain, Manjeet Singh (Indian Journal of Extension Education, 2023)
Editorial In concern to raising agricultural productivity per unit of land; reducing rural poverty through a socially inclusive strategy; agricultural growth corresponding to food security needs; and sustaining the environment the factors such as land tenancy, the system of ownership, size of holdings, availability of labour and capital, religion, level of technological development, accessibility to the market, irrigation facilities, agricultural research, and extension service, price incentives, government plans, and international policies have a close impact on agricultural activities. Agricultural extension has evolved as a holistic discipline of facilitating farmers’ welfare and sustainable agricultural growth. Amidst the emerging dynamics, of the demand for more income from an existing piece of land, and the increased demands for value-added food commodities in the market; secondary agriculture may offer solutions to challenges in agriculture. The Indian Society of Extension Education (ISEE), New Delhi has planned it’s National Seminar 2023 on ‘Evolving Extension Science Towards Secondary Agriculture for Sustainable Development’ to be held at the University of Agricultural Sciences, Bangalore during June 22-24, 2023. It will be a great occasion as the ISEE will be celebrating its 60th year of inception on the inaugural day of the National Seminar. The major themes planned around the secondary agriculture involve; historical footprints to modern practices and innovations; Enterprise diversification for enhancing productivity and farm income; policy initiatives and institutional role; global good management practices; leveraging social media and ICT interventions; innovative extension science methodologies; entrepreneurship development and human resource development; gender mainstreaming and FPOs, CBOs and other governmental initiatives. The details of the seminar, crucial dates, etc can be accessed www.iseenationalseminar2023.in or http://www.iseeiari.org/news/isee-national-seminar-2023/ The current issue (April-June, 2023) contains 32 manuscripts including four research tools, six research notes, and twenty-two full-length research papers from cross-sectional authors and content. The measuring tools include; women empowerment in aquaculture, farmers’ knowledge on the management of parasitic infestation in dairy animals, the attitude of farmers toward conservation agriculture, and the attitude of farm families toward gender equity. The manuscripts on constraints in geographical indication authorized user registration and usage, climate change adaptation constraints among paddy farmers, wildlife conflict and prevention strategies adopted by farmers and forest officials, utilization pattern of ICT tools, analyzing the feedback from women dairy farmers, and constraints faced by tomato growers at production and marketing level made the ‘Research Note’ section. The determinants of ; Climate change adaptation, composite livelihood security, entrepreneurial climate and attributes of agripreneurs; Efficiency of Pineapple Production and FPOs performance; descriptive analysis of attitude towards students READY programme entrepreneurial competencies generated through ARYA; entrepreneurial aptitude of women of an aspirational district; CoVID-19 lockdown effect on the investment and profitability; agricultural credit utilization and repayment by farm households; personal behaviour influence on adoption of climate change mitigating measures; impact of ; climate resilient technological interventions, CFLDs on pigeon pea productivity and profitability; adoption behaviour of climate-resilient agricultural practices, economic analysis and resource use efficiency in cotton production, yield gaps and scaling up of sesame variety; experimental study on enhancing effectiveness of farm school through community wall magazine; gender- based variations in perception of flood impacts, farmers’ awareness of agricultural schemes under saansad adarsh gram yojana; perception of KVK professionals on objectives of extension education, professional competence of extension personnel and finally application of nudge theory to document ICT initiatives of agricultural research institutions were covered in ‘Research Article’ section. As usual, the data is regularly being fed to international indexing agencies leading to the indexing of the Indian Journal of Extension Education at Index Copernicus International Journal Master list, CAB International; ICI; BASE; Google scholar; Scilit; Semantic Scholar; WorldCat; Science gate; Agricultural Science and Technology Information database of FAO and Crossref. From January 2023, the journal has been inducted into the UGC CARE List which has brought another responsibility to deal with unrelated submissions in glut. I extend sincere thanks to all the expert members of the editorial board for their painstaking efforts. The reviewing contributions of not only the editorial team members but many willful contributors are sincerely acknowledged. I extend my sincere thanks to all the authors for making valuable contributions. The support extended by Executive Council is duly acknowledged. The editorial team also congratulates the President ISEE; Dr. U. S. Gautam on his taking over as Deputy Director General (Agricultural Extension at the Indian Council of Agricultural Research New Delhi. Special thanks are extended to the President, ISEE; Dr. U.S. Gautam, Secretary ISEE; Dr. Rashmi Singh, Treasurer, ISEE; Dr. B. K. Singh and Joint Secretary, ISEE; Dr. J. S. Malik for providing insightful thoughts and guidance in bringing out this issue. Dr. Bhanu P. Mishra, Vice President (Central Zone) deserves special thanks for making committed efforts at all stages of ISEE matters. (Manjeet Singh Nain)